Ritual Motasu (Penanaman Padi) pada Masyarakat Tolaki di Desa Buke Kecamatan Buke Kabupaten Konawe Selatan - Putri Yani; Rahmat Sewa Suraya; La Ode Marhini (Jurusan Tradisi Lisan, Fakultas Ilmu Budaya, Univeritas Halu Oleo, 2023)
The purpose of this research is to describe the implementation process, utterances and functions contained in the Motasu ritual. This research was conducted in Buke Village, Buke District, Konawe Selatan Regency from February to March 2023 using a qualitative approach. The results of this research show that the Motasu ritual process goes through three stages, namely the preparation stage, the implementation stage and the final stage. In every process carried out in the Motasu ritual, there are utterances and functions that contain certain meanings. The function contained in the Motasu ritual is a form of interpretation in asking for protection from the ruler of the forest (the Unseen realm). As seen until now, the Motasu ritual still survives and continues to be carried out in the life of the Tolaki people.